The Impact of Forced Transitions on the Most Functionally Impaired Nursing Home Residents - Thomas, Kali S. (2012)
BACKGROUND/OBJECTIVES: To examine the hospitalization rate and mortality associated with forced mass transfer of nursing home residents with the highest levels of functional impairment. DESIGN: Retrospective cohort study. SETTING: 119 Texas and Louisiana nursing homes that were identified as being “at-risk” for evacuation for Hurricane Gustav. PARTICIPANTS: 6,464 long-stay residents residing in “at-risk” nursing homes for at least three consecutive months prior to landfall of Hurricane Gustav. MEASUREMENTS: Using Medicare claims and instrumental variable analysis, we compared the differential mortality (death at 30 and 90 days) and hospitalization rates (at 30 and 90 days) of the most functionally-impaired long-stay residents who evacuated for Hurricane Gustav relative to the most functionally impaired residents who did not evacuate. RESULTS: Results suggest that the effect of evacuation was associated with an 8% increase in hospitalizations by 30 and 90 days for the most functionally impaired residents. Evacuation was not significantly related to mortality for the most functionally impaired residents. CONCLUSION: Our results suggest that the most functionally impaired nursing home residents experience an increase in hospitalizations but not mortality as a consequence of forced mass transfer. With the inevitability of nursing home evacuations for many different reasons, harm mitigation strategies focused on the most impaired residents are needed.